Diskursus Ruang Publik Habermasian dan Kebijakan Publik: Studi Literatur - Triguswinri, Krisnaldo (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2023)
In previous research, several researchers argued that public sphere as a space for community participation can be a very influential approach in policy decision-making process. While the other researchers argue that public sphere is important informal space which connects people’s democratic rights with the process of making policies regarding to public wants. This paper uses qualitative approach, with the data collection technique is literature study. The writer analyzes 11 international articles and 3 national articles which is correlated to the influenxe of civil society ini public sphere towards public policy. Keywords: Habermas, public Sphere, Civil Society, Public Policy